Engineering patient-specific bioprinted constructs for treatment of degenerated intervertebral disc - Costa, João Bebiano; Silva-Correia, Joana; Ribeiro, Viviana Pinto; da Silva Morais, Alain; Oliveira, Joaquim Miguel; Reis, Rui Luís (Materials today communications, 2019)
[Display omitted] Lower back pain (LBP), which is strongly associated with intervertebral disc (IVD) degeneration, is one of the most frequently reported age- and work-related disorder in actual society, leading to a huge socio-economic impact worldwide. The current treatments have poor clinical outcomes and do not consider each patient needs. Thus, there is a growing interest in the potential of personalized cell-based tissue engineering (TE) approaches aimed to regenerate the damaged IVD and efficiently restore full disc function. In this work, a bioink composed by silk fibroin (SF) hydrogel combined with elastin was used to bioprint patient-specific substitutes mimicking IVD ultrastructure, in particular the outer region of the IVD (i.e. annulus fibrosus, AF). Following a reverse engineering approach, the proposed strategy makes use of a 3D model of AF obtained by semi-automatic morphological segmentation from magnetic resonance imaging dataset of human IVD. SF/elastin bioprinted scaffolds were characterized thoroughly in vitro, in terms of physico-chemical and biological performance. The bioprinted SF/elastin scaffolds were shown to possess structural and mechanical properties similar to the native AF and to support cell attachment and growth. Human adipose-derived stem cell cultured onto the SF/elastin bioprinted scaffolds were shown to adhere, proliferate and maintain metabolic activity and viability up to 21 days of culturing. The implantation of custom-made SF/elastin implants that best emulate a patient AF anatomy can potentially open up new personalized treatments for tackling IVD disorders by means of improving recovery time after surgery and helping to restore spine biofunctionality.